The Process of the Intergenerational Succession of Leadership in a Family Business - Bojan Dolar; Roberto Biloslavo (Economic and Business Review, 2023)
Background and objective: In this paper, we explore first-generation leadership succession in family businesses which, despite extensive literature on the subject, remains insufficiently understood. Our goal is to acquire new knowledge and understanding regarding this phenomenon with a view to making it more effective. Method: The basis of our research is a qualitative multiple case study that includes six medium-sized manufacturing family businesses. We conducted semi-structured interviews with incumbents, successors and family representatives, and analysed the data obtained using the content analysis method. Results: The data analysis and interpretation led to a definition of the category “The way ahead: the process of succession” along with descriptions of its nine elements that help answer three research questions. Conclusions: The research results show significant differences between the processes considered together with their uniqueness. While the need for succession planning and plan preparation is clearly expressed, no steps are taken due to the underestimation of its importance, the lack of both experience and relevant knowledge, often accompanied by emotional burdens that discourage planning. Contribution: The study contributes original insights and new knowledge concerning the leadership succession process, succession planning, and its implementation.